STUDI NASKAH FIKIH MELAYU (RISALAH IS’AF AL RAGHIBIN FI ‘ILMI AL FARAIDH) KARYA JAD AHMAD MUBARAK - Wahidah, Wahidah (Pascasarjana UIN ANTASARI Banjarmasin, 2019)
Jad Ahmad Mubarak is a title that was deliberately chosen by the composer of Risalah Is'af al Raghibin fi ?Ilmi al Faraidh. The name is indeed not found in any one site, but the teacher and caretaker of Al Mursyidul Amin Islamic Boarding School has experience and deep understanding on Fiqh Mawarits. This handwritten work is not widely known by the Banjar Muslim community. So, this paper discusses the